Analisis Efisiensi Pemasaran Tandan Buah Segar Perkebunan Kelapa Sawit Pola Kemitraan dan Pola Swadaya di Kabupaten Tanjung Jabung Barat - Irzi, Haykal; Nainggolan, Saidin; Saputra, Ardhiyan; Ulma, Riri Oktari (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
This study aims to (1) describe the marketing channels of fresh fruit bunches (FFB) of oil palm under partnership and independent (self-managed) schemes in Merlung District, Tanjung Jabung Barat Regency; (2) analyze marketing margins, farmer’s share, and marketing efficiency for each scheme; and (3) compare differences in marketing margins and farmer’s share between single-level marketing channels in both business schemes. The research was conducted in 2025 using a survey method with simple random sampling techniques. The data used consisted of primary data obtained through direct interviews with farmers and marketing institutions, as well as secondary data from relevant agencies. Data analysis was carried out using descriptive analysis, marketing margin analysis, farmer’s share, marketing efficiency analysis, and Multivariate Analysis of Variance (MANOVA). The results show that there are two types of marketing channel patterns, namely single-level and two-level channels. The single-level marketing channel has lower marketing margins, higher farmer’s share, and better marketing efficiency. In addition, there are significant differences between single-level marketing channels in both business schemes. These findings imply that shorter marketing channels are more efficient and provide a greater share of the selling price to smallholder oil palm farmers